Economic growth in Brazil: an approach about capital accumulation and institutions - Bondezan, Kezia de Lucas; Dias, Joilson (Revista Econômica do Nordeste, 2017)
This article contributes to the discussion of the relation between human capital, institutions and economic growth. First it is presented the micro foundations that link the institutions to human capital, according to Dias and Tebaldi (2012). The advantage of modeling this strategy is that the accumulation of human capital is derived from an endogenous process. The theoretical model shows that improvements in the quality of institutions turn the accumulation of human capital faster, reduce income inequality and change the historical path of development. The differential about this article is that it uses a panel of data from Brazilian states in the period from 2002 to 2008, for testing some prepositions of the model and finds that structural and political institutions affect the long-term performance of the economy.